Design of a compact quad‐band antenna with independent frequency tuning. Issue 15 (1st July 2018) - Islam, Sk.N.; Kumar, M.; Sen, G.; Das, S.
Abstract : A compact, planar, low profile microstrip line‐fed quad‐band antenna is presented with operating frequencies at 2.5/3.6/5.5/7.5 GHz. The antenna consists of a rectangular split‐ring resonator (SRR), a stepped impedance resonator (SIR) inside the ring, a slot on the SIR and a pair of SRRs either side of the matching network. Each of the resonators generates its own individual band which is independently tunable. The antenna is compact in size having dimensions 0.10 λ 0 × 0.13 λ 0 . The radiation patterns are omnidirectional and bilateral in the H ‐plane and the E ‐plane, respectively, at all the resonance frequencies. The simulated results are observed and reported in terms of S ‐parameters, gain and radiation patterns. A prototype structure is fabricated and the measured results are compared with those obtained from the simulation.